El uso de las TIC´S como herramienta de apoyo de los docentes en la elaboración de insumos pedagógicos - Arias Cornejo, Juan Carlos (2021)
In this research we address the use of ICTs as a tool to support the teacher in the development of pedagogical inputs, currently virtual platforms play a fundamental role in education worldwide since it allows the teacher to direct a class With their students regardless of the geographical location of each one, these ICTs facilitate the learning process and facilitate the creation of pedagogical inputs that serve to improve collective learning. ICTs is not a term that just appears at the moment that we are experiencing the global pandemic due to Covid-19, this term has its origin since the 70's when the digital revolution began to explode. The tic's are tools that allow us to transmit information through communications, that is why in times of mandatory confinement due to the pandemic these Tic's did not allow to continue studying despite being at home, even the tic's too They helped companies to continue working through teleworking. In education, ICTs help to improve the learning process because it allows us to share resources such as videos, slides, PDF files, among other educational supplies.